A Waste-to-Energy Technical Approach: Syngas–Biodiesel Blend for Power Generation - Arruda Ferraz de Campos, Victor [UNESP]; Carmo-Calado, Luís; Mota-Panizio, Roberta; Matos, Vitor; Silva, Valter Bruno; Brito, Paulo S.; Eusébio, Daniela F. L.; Tuna, Celso Eduardo [UNESP]; Silveira, José Luz [UNESP] (MDPI, 2023)
In this study, a technical analysis of synthesis gas (syngas) and biodiesel blend utilized in an internal combustion engine is presented. The experimental setup is composed of an engine workbench coupled with a downdraft gasifier which was fed with forest biomass and municipal solid waste at a blending ratio of 85:15, respectively. This research paper aims to contribute to the understanding of using fuel blends composed of synthesis gas and biodiesel, both obtained from residues produced in a municipality, since the waste-to-energy approach has been trending globally due to increasing waste generation allied with rising energy demand. The experiments’ controlling parameters regarding the engine are rotation and torque, exhaust gas temperature, and fuel consumption. The gasification parameters such as the oxidation and reduction temperatures, pressures at the filter, hood, and reactor, and the volume of tars and chars produced during the thermochemical process are also presented. Ultimate and proximate analyses of raw materials and fuels were performed, as well as the chromatography of produced syngas. The syngas produced from forest biomass and MSW co-gasification at a blending ratio in mass of 85:15 presented an LHV of around 6 MJ/m3 and 15% of H2 in volume. From the experiment using syngas and biodiesel blend in the engine, it is concluded that the specific consumption at lower loads was reduced by 20% when compared to the consumption of the same engine operating with regular diesel. The development of co-gasification of forest and municipal waste may then be an interesting technology for electrical energy decentralized generation.
Keywords: biodiesel; fuel blend; gasification; syngas; waste-to-energy